Comparison of the Outcomes of Open versus Minimally Invasive Spinal Surgery for the Treatment of Thoracolumbar Traumatic Spinal Injury - Mughis, Waqas; Waheed, Usamah bin; Aziz, Moiz; Shibli, Zaheen; Ruba; Khatri, Muhammad Adil (Indus Journal of Bioscience Research, 2025)
Objective: To compare the outcomes of open versus minimally invasive spinal surgery for the treatment of thoracolumbar traumatic spinal injury. Study Design and Setting: Descriptive observational study was conducted at the department of Neurosurgery, Civil Hospital Karachi for the duration six months from January 1, 2020 to June 30, 2020. Subjects and Method: A total of sixty consenting patients of either gender of patients between ages 18-75 years diagnosed as thoracolumbar traumatic spinal injury (TLSI) underwent for surgical decompression, fusion or stabilization with pedicular screw fixation with open or minimally invasive spinal surgery (MISS) were included. These patients were divided into two groups via lottery method. Laminectomy in either group was done if needed. Surgery was performed by experienced neurosurgeons in presence of researcher. The findings like intra operative blood loss, operative time, post-operative hospital stay in days and Oswestry Disability Score on 1 month follow-up) was noted. Data was analyzed by using SPSS 26.0. Results: Age range in this study was from 18 to 75 years. Mean age in open group was 56.6 ± 14.6years and in MISS group was 52.2 ± 13.8 years. Significant difference was observed in intra-operative blood and operative time and no significant difference was observed in duration of hospital stay and Oswestry Disability score. Conclusion: Our study documents favorable patient and radiographic outcomes with the use of MISS for thoracolumbar trauma.